Multi-Temporal Landslide Inventory-Based Statistical Susceptibility Modeling Associated With the 2017 Mw 6.5 Jiuzhaigou Earthquake, Sichuan, China - Luo, Luguang; Pei, Xiangjun; Zhong, Chuangui; Yang, Qingwen; Fan, Xuanmei; Zhu, Ling; Huang, Runqiu (Frontiers in Environmental Science, 2022)
The 2017 Mw 6.5 Jiuzhaigou earthquake (Sichuan, China) is the first strong ground motion strike the famous world heritage site in the world, causing widespread landslides and severe rock masses damage and landscapes undergoing rapid evolution in Jiuzhaigou National Geopark. However, the understanding of the variability of pre-and post-earthquake landslide susceptibility and landslide conditioning factor effects over time remains limited. This study aims to carry out multi-temporal statistical landslide susceptibility modeling at the slope-unit level related to this event. To achieve this, we initially used a set of remote sensing imageries in GIS to obtain systematic landslide inventories across the pre-, co-, and post-seismic periods. Based on three landslide inventory datasets, we developed three statistical models by incorporating 14 landslide conditioning (seismic, topographic, and geologic) factors into a Binary Logistic Regression (BLR) model. Finally, we utilized the area under the receiver operating characteristic (AUC) curve to assess each model’s calibration and validation performance. The results show that the BLR model has good prediction applicability for both normal and seismic landslides in the study area with outstanding to excellent predictive accuracy for Mod1 (pre-seismic, AUC=0.801), Mod2 (co-seismic, AUC=0.942), and Mod3 (post-seismic, AUC=0.880). There are variations in both the importance of landslide conditioning factors and susceptibility maps through time, and the number of slope units with mean probability over 0.8 from only one (pre-seismic) increased to 21 (post-seismic). The dynamic susceptibility maps are of great significance for identifying potentially unstable slopes and providing references for hazard and risk assessment, which could provide new insights into geo-environmental protection and regional landslide evaluation in scenery spots, even for those world heritage sites in the tectonic active mountainous region. And, more frequent or extended observation periods could contribute a further understanding of the post-seismic landslide developments for the Jiuzhaigou area,